ETNOMATEMATIKA PADA BANGUNAN TEMPAT IBADAH TRI DHARMA HOO TONG BIO BERDASARKAN KONSEP GEOMETRI SEBAGAI BAHAN AJAR SISWA - Afifi, Rizky Nur; Trapsilasiwi, Dinawati; Yudianto, Erfan (Kadikma, 2019)
The purpose of this study was to describe ethnomatematics in the Tri Dharma Hoo Tong Bio Place of Worship building and produce student teaching materials in the form of student worksheets. This type of research is qualitative research with an ethnographic approach. Data collection methods used are observation and interviews. The subjects of this study were one religious leader and one handyman. Ethnomatematics that appear in the Tri Dharma Hoo Tong Bio Places of Worship building are found in several building forms and building sizes. This study focused on several objects. The object in question is the Pagoda, Jin-Lu, Genta, Tambun. The mathematical concepts that emerged in the building of the Place of Worship Tri Dharma Hoo Tong Bio are geometric forms, congruent, similarity and transformation of geometry. Student worksheets are intended for class VIII Middle School / MTs students with material to construct flat side spaces. Keywords: Ethnomatematics, TITD Hoo Tong Bio, Geometry